Change in consolidated business models: the study of Radio Taxi cooperatives in Brazil after the inclusion of mobile applications in the market - Hino, Marcia Cassitas; Bono Milan, Luiz Fernando A.; Cunha, Maria Alexandra Viegas Cortez da; Meirelles, Fernando S. (Journal of Information Systems and Technology Management, 2018)
AbstractProliferation of mobile applications modified the taxi cooperative business model. The objective of this research was to verify how the changes in such business model occurred in a scenario of innovation,enhanced by the use of technology. The Pluralist and Multilevel Conceptual Solution was the theoretical lens selected for a qualitative study that covered the cities of São Paulo and Curitiba. Users and managers of cooperatives and applications were interviewed as well as taxi drivers. The most significantcontribution of the work is the demonstration of how technology can modify an established business model.Keywords: Radio taxi applications, Taxi cooperative, Information technology, ICT, Business model.RESUMOO modelo de negócio de cooperativa de táxis foi modificado com a proliferação de aplicativos móveis. O objetivo desta pesquisa foi verificar como se deram as mudanças em um modelo de negócio num cenário de inovação, potencializado pelo uso da tecnologia. A Solução Conceitual Pluralista e Multinível foi a lente teórica selecionada para um estudo qualitativo que abrangeu as cidades de São Paulo e Curitiba. Foram entrevistados usuários e gestores de cooperativas e aplicativos, bem como taxistas. A contribuição mais significativa do trabalho é a demonstração de como a tecnologia pode modificar um modelo de negócios estabelecido.Palavras-chave: Aplicativos de rádio táxis, Cooperativa de táxis, Tecnologia da informação, TIC, Modelo de negócio.